Technology, education and critical media literacy: potential, challenges, and opportunities - Mayte Santos Albardía; Simón Peña-Fernández; Irati Agirreazkuenaga (Frontiers in Human Dynamics)
This study examines the impact of technology within media education, media literacy, and educommunication, and explores how these fields are perceived and understood by students and academic experts, focusing on the development of critical competencies and critical media literacy. Based on semi-structured in-depth interviews with leading experts in the field of critical media literacy, and a survey conducted with 141 university students in Communication and Education programs, this study explores how recent technological advances are linked to challenges in information consumption—such as disinformation, fake news, incidental exposure to information, and deepfakes—as well as the challenges and opportunities these issues present within educational contexts. The results reveal that, although such technologies provide opportunities to improve teaching–learning processes, their inclusion in the curriculum is limited and often superficial. In addition, we identify shortcomings in how teachers are trained to manage these tools effectively, hindering the development of critical thinking by students. The conclusions suggest a need for critical media literacy that not only educates students in the use of technologies but also allows them to question and evaluate the content they consume, all within an ethical and reflective framework that promotes participatory and critical citizenship.